Development, Characterization and Application of Microsatellite Markers of Mangrove Horseshoe Crab, Carcinoscorpius Rotundicauda Latreille in Peninsular Malaysia - Abu Bakar, Adibah (2011)
Horseshoe crab populations are said to be declining worldwide. However, there is still no published report on the status of horseshoe crabs in Malaysia. In this study, microsatellite markers were developed using 5‟anchored ISSR-PCR enrichment procedure to diagnose population genetic structure of the mangrove horseshoe crab, Carcinoscorpius rotundicauda. A total of 134 microsatellite regions have been succesfully isolated using this technique and 36 novel microsatellite markers were developed. Out of these, eleven informative microsatellite loci were identified in an analysis of 127 samples representing five C. rotundicauda populations namely Kuala Juru, Kg. Permatang, Kg. Chuah, Kg. Sekokoh and Kg. Sg. Pulai from Peninsular Malaysia. The mean expected (He) and observed heterozygosity (Ho) values obtained ranged between 0.299-0.421 and 0.148-0.197 respectively. Significant departures from Hardy-Weinberg equilibrium were detected in C. rotundicauda populations at Kg. Permatang, Kg. Chuah and Kg. Sg. Pulai. These populations also show moderate genetic differentiation with overall FST values of 0.108. Pairwise genetic distance values analysed between the five populations studied were close to zero which indicate high genetic similarity between populations. Five polymorphic inter-simple-sequence-repeat (ISSR) markers tested also generated comparable results. Thus, samples in each population are presumed to be genetically similar although the populations studied were geographically distant. Due to the unknown migratory ability of C. rotundicauda species, existing habitats must be conserved for the survival of this species especially in Peninsular Malaysia. Findings from this study provide information on the genetic diversity of C. rotundicauda in Peninsular Malaysia and are hoped to assist in the development of conservation program for the mangrove horseshoe crabs in Southeast Asia.